Polyamide-like covalent organic framework diaphragm for vanadium battery and preparation method of polyamide-like covalent organic framework diaphragm

The preparation of polyamide-like covalent organic frame films through solvent thermal oxidation and interfacial polymerization has solved the problem of excessive pore size of vanadium battery membranes in the prior art, improved the voltage and Coulomb efficiency of vanadium battery, and achieved higher Ion selectivity and battery performance.

CN119315051AInactive Publication Date: 2025-01-14HANGZHOU DEHAI AIKE ENERGY TECH CO LTD

Patent Information

Application Number
CN202411833091.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The micelle channel size of the existing perfluorosulfonic acid film is large, resulting in low Coulombic efficiency and fast capacity decay, hindering the large-scale application of all vanadium flow batteries, and the pore size of the two-dimensional covalent organic frame is too large. , cannot effectively block vanadium ions and has low efficiency in conducting protons.

Method used

The polyamide-like covalent organic frame nanosheet dispersion was prepared by solvent thermal oxidation, and a polyamide-like covalent organic frame film with multi-stage pore effect was generated through interfacial polymerization, which was used for porous vanadium liquid flow battery. Proton exchange membrane.

Benefits of technology

The proton conductivity and ion selectivity of the membrane are improved, the voltage efficiency and Coulomb efficiency of vanadium batteries are enhanced, the effective aperture is reduced, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315051A_ABST
    Figure CN119315051A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flow battery diaphragms, and discloses a polyamide-like covalent organic framework diaphragm for a vanadium battery and a preparation method of the polyamide-like covalent organic framework diaphragm. Comprising the following steps: preparing a porous base membrane; preparing covalent organic framework nanosheet dispersion liquid by a solvothermal oxidation method; preparing a two-phase solution of interfacial polymerization; and preparing the polyamide-like covalent organic framework diaphragm. The processability of the covalent organic framework can be improved by a solvothermal oxidation method. The polyamide-like covalent organic framework diaphragm has high porosity, and pore channels are rich in sulfonic acid groups, so that the proton conductivity of the diaphragm can be improved. In addition, the polyamide-like covalent organic framework diaphragm has intrinsic pore channels of a covalent organic framework and polyamide pore channels, the effective pore diameter is reduced through a hierarchical pore effect generated by staggered arrangement of the intrinsic pore channels and the polyamide pore channels, and the ion selectivity of the diaphragm and the coulombic efficiency of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid flow battery diaphragms, and in particular to a polyamide-type covalent organic framework diaphragm for a vanadium battery and a preparation method thereof. Background Art

[0002] Liquid flow batteries are energy storage devices that realize the mutual conversion of electrical energy and chemical energy. Unlike traditional batteries that store energy in electrode materials, liquid flow batteries store energy in two pairs of soluble redox pairs. All-vanadium liquid flow batteries are typical representatives of liquid flow batteries. They only use a single transition metal element, vanadium, and use four vanadium ions of different valence states as redox pairs to store and release electrical energy. They have the advantages of flexible design, high efficiency, long life, high safety factor, and environmental friendliness.

[0003] The diaphragm is an important component of vanadium batteries. It plays a role in blocking the shuttle of vanadium ions and conducting protons, which is crucial to the stable operation of vanadium batteries. The development of diaphragms with good performance and low cost is a key factor in the development of vanadium batteries. The perfluorosulfonic acid ion exchange membrane is composed of hydrophilic polymer side chains and hydrophobic polymer main chains. It has micellar channels for proton conduction, high ion conductivity, and good electrochemical performance and chemical stability. Therefore, it has become the most widely used ion exchange membrane in the field of vanadium batteries. However, the micellar channel size of the perfluorosulfonic acid membrane is large, about several microns, so there are problems such as low ion selectivity, resulting in low coulombic efficiency and rapid capacity decay of the battery, which in turn hinders the large-scale application of all-vanadium liquid flow batteries.

[0004] Covalent organic frameworks (COFs) are a new type of crystalline polymer material, which is formed by copolymerization or self-polymerization of organic small molecules and connected by covalent bonds. They have the characteristics of low density, high specific surface area, high porosity, adjustable pore size and controllable properties in the pores, and have great application prospects in the fields of adsorption, catalysis, conduction and separation. However, the theoretical pore size of most reported two-dimensional covalent organic frameworks is still too large compared to the hydration diameter of vanadium ions, and the barrier effect on vanadium ions is still unsatisfactory; on the other hand, most unmodified covalent organic frameworks lack proton-conducting groups and can only conduct protons through high porosity. Therefore, it is difficult to simultaneously improve the coulombic efficiency and voltage efficiency of vanadium batteries based on their intrinsic pore structure alone, which hinders their application in the field of liquid flow batteries. Summary of the invention

[0005] The present invention provides a polyamide-like covalent organic framework diaphragm for vanadium battery and a preparation method thereof, and prepares a covalent organic framework diaphragm with a polyamide-like structure. A covalent organic framework nanosheet dispersion is prepared in one step under the conditions of solvent thermal and mild oxidation (i.e., "solvothermal oxidation method") using amine monomers rich in sulfonic acid groups, and an aqueous phase solution of interfacial polymerization polyamide reaction is obtained by dialysis with deionized water. The unreacted amino groups at the edge of the nanosheet are reacted with a polyacyl chloride crosslinking agent to generate a nanosheet crosslinked body structure with a polyamide-like structure, and then a polyamide-like covalent organic framework membrane is prepared with a porous base membrane by suction filtration, and the membrane is used for a porous proton exchange membrane of an all-vanadium redox flow battery.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery comprises the following steps: S1. Preparation of porous base membrane: dissolve the polymer in solvent 1 to prepare a casting solution with a mass fraction of 10-20%. Prepare the polymer porous membrane by non-solvent induced phase separation (NIPS) and use it as the porous base membrane for preparing polyamide-type covalent organic framework membrane.

[0007] S2. Preparation of covalent organic framework nanosheet dispersion by solvent thermal oxidation method: 1-5 parts by mass of amine monomer containing sulfonic acid group, 1.5-7.5 parts by mass of aldehyde monomer and 0.1-0.5 parts by mass of oxidant are dispersed in 1000-5000 parts by mass of solvent 2, and heated to react at 80-150°C for 24-72 hours to obtain covalent organic framework nanosheet dispersion.

[0008] S3, preparing a two-phase solution for interfacial polymerization: centrifuging the covalent organic framework nanosheet dispersion in S2 at a speed of 6000-10000 rpm for 5-15 minutes, taking the supernatant and dialyzing it with pure water at room temperature for 12-36 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, 0.8-3 parts by mass of a polyacyl chloride crosslinking agent is dispersed in 1000-5000 parts by mass of solvent 3 as an organic phase solution.

[0009] S4. Preparation of a polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 300-500 parts by mass of an aqueous solution, and then drop 300-500 parts by mass of an organic solution onto the surface of the aqueous solution to form an interface. After standing for 1-10 minutes at room temperature, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface onto the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 60-80°C for 5-15 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0010] Preferably, the polymer in step S1 is selected from one of polyacrylonitrile, polyimide, polyvinylidene fluoride, polytetrafluoroethylene and polyether sulfone.

[0011] Preferably, in step S1, the solvent 1 is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0012] Preferably, the amine monomer containing a sulfonic acid group in step S2 is selected from one of 2,5-diaminobenzenesulfonic acid, 2,5-diamino-1,4-benzenedisulfonic acid, 4,4'-diaminobiphenyl-3-sulfonic acid and 4,4'-diaminobiphenyl-3,3'-disulfonic acid.

[0013] Preferably, the aldehyde monomer in step S2 is selected from one of trimesaldehyde, 2-hydroxy-1,3,5-benzenetricarbaldehyde, trialdehyde phloroglucinol, 2,4,6-trialdehyde-1,3,5-triazine and 1,3,5-tris(4'-formylphenyl)benzene.

[0014] Preferably, in step S2, the oxidant is selected from one of dimethyl sulfoxide, thionyl chloride, diphenyl sulfone, diethyl sulfone and dibutyl sulfone.

[0015] Preferably, in step S2, the solvent 2 is selected from one of mesitylene, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide and trichloroacetic acid.

[0016] Preferably, in step S3, the polyacyl chloride cross-linking agent is selected from one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, 3,3',5,5'-biphenyltetracarboxylic acid chloride and malonyl chloride.

[0017] Preferably, in step S3, the solvent 3 is selected from one of n-hexane, n-butane, cyclopentane, o-xylene and n-octanoic acid.

[0018] The beneficial effects of the present invention are: The solvent thermal oxidation method used in the present invention can realize the transformation from monomers to covalent organic framework nanosheets in one step, thereby improving the processability of the covalent organic framework.

[0019] The polyamide-type covalent organic framework diaphragm prepared by the invention has high porosity and is rich in sulfonic acid groups in the pores, which can improve the proton conductivity of the membrane and further improve the voltage efficiency of the vanadium battery.

[0020] The polyamide-like covalent organic framework diaphragm prepared by the invention has intrinsic pores of the covalent organic framework and polyamide pores, and the multi-level pore effect generated by the staggered arrangement thereof reduces the effective pore size, thereby improving the ion selectivity of the membrane and the coulomb efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the preparation of the polyamide-type covalent organic framework membrane of the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the covalent organic framework nanosheet in Example 1 of the present invention; Figure 3 This is a SEM image of the covalent organic framework nanosheet in Example 2 of the present invention; Figure 4 Surface and cross-sectional scanning SEM images of the covalent organic framework membrane in Example 3 of the present invention. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0023] A method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery comprises the following steps: S1. Preparation of porous base membrane: dissolve the polymer in solvent 1 to prepare a casting solution with a mass fraction of 10-20%. Prepare a polymer porous membrane by non-solvent induced phase separation, and use it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane. The polymer is selected from one of polyacrylonitrile, polyimide, polyvinylidene fluoride, polytetrafluoroethylene and polyether sulfone. Solvent 1 is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0024] S2. Preparation of covalent organic framework nanosheet dispersion by solvent thermal oxidation method: 1-5 parts by mass of amine monomer containing sulfonic acid group, 1.5-7.5 parts by mass of aldehyde monomer and 0.1-0.5 parts by mass of oxidant are dispersed in 1000-5000 parts by mass of solvent 2, and heated at 80-150°C for 24-72 hours to obtain covalent organic framework nanosheet dispersion. The amine monomer containing sulfonic acid group is selected from one of 2,5-diaminobenzenesulfonic acid, 2,5-diamino-1,4-benzenedisulfonic acid, 4,4'-diaminobiphenyl-3-sulfonic acid and 4,4'-diaminobiphenyl-3,3'-disulfonic acid. The aldehyde monomer is selected from one of trimesic acid, 2-hydroxy-1,3,5-benzenetricarbaldehyde, trialdehyde phloroglucinol, 2,4,6-trialdehyde-1,3,5-triazine and or 1,3,5-tris(4'-formylphenyl)benzene. The oxidant is selected from one of dimethyl sulfoxide, thionyl chloride, diphenyl sulfone, diethyl sulfone and dibutyl sulfone. The solvent 2 is selected from one of mesitylene, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide and trichloroacetic acid.

[0025] S3, prepare a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 6000-10000 rpm for 5-15 minutes, take the supernatant and dialyze it with pure water at room temperature for 12-36 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, 0.8-3 parts by mass of a polyacyl chloride crosslinker is dispersed in 1000-5000 parts by mass of solvent 3 as an organic phase solution. The polyacyl chloride crosslinker is selected from one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, 3,3',5,5'-biphenyltetracarboxylic acid chloride and malonic acid chloride. Solvent 3 is selected from one of n-hexane, n-butane, cyclopentane, o-xylene and n-octanoic acid.

[0026] S4. Preparation of polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour 300-500 parts by mass of aqueous solution, and then slowly drop 300-500 parts by mass of organic solution onto the surface of the aqueous solution to form an interface. After standing for 1-10 minutes at room temperature, open the valve at the bottom of the reactor and connect the vacuum pump, filter the thin film at the interface to the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 60-80°C for 5-15 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0027] Example 1: The following preparation scheme is used to obtain S1. Preparation of porous base membrane: dissolve polyacrylonitrile in N,N-dimethylformamide to prepare a casting solution with a mass fraction of 10%. Prepare a polymer porous membrane by non-solvent induced phase separation, and use it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2. Preparation of a covalent organic framework nanosheet dispersion by a solvent thermal oxidation method: 1 part by mass of 2,5-diaminobenzenesulfonic acid, 1.5 parts by mass of trimesaldehyde and 0.5 parts by mass of dimethyl sulfoxide are dispersed in 1000 parts by mass of mesitylene, and heated at 80° C. for 24 hours to obtain a covalent organic framework nanosheet dispersion; S3, preparing a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 6000 rpm for 5 minutes, take the supernatant and dialyze it with pure water at room temperature for 12 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, disperse 0.8 parts by mass of trimesoyl chloride in 1000 parts by mass of n-hexane as an organic phase solution; S4. Preparation of a polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 300 parts by mass of an aqueous solution, and then slowly drop 300 parts by mass of an organic solution onto the surface of the aqueous solution to form an interface. After standing at room temperature for 1 minute, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface onto the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 60°C for 5 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0028] Example 2: The following preparation scheme is used to obtain S1. Preparation of porous base membrane: dissolve polyvinylidene fluoride in N,N-dimethylacetamide to prepare a casting solution with a mass fraction of 13%. Prepare a polymer porous membrane by non-solvent induced phase separation, and use it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2. Preparation of a covalent organic framework nanosheet dispersion by a solvent thermal oxidation method: 2 parts by mass of 2,5-diamino-1,4-benzenedisulfonic acid, 3 parts by mass of 2-hydroxy-1,3,5-benzenetricarboxaldehyde and 0.4 parts by mass of thionyl chloride are dispersed in 2000 parts by mass of dioxane, and heated at 100° C. for 72 hours to obtain a covalent organic framework nanosheet dispersion; S3, preparing a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 7000 rpm for 10 minutes, take the supernatant and dialyze it with pure water at room temperature for 18 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, disperse 3 parts by mass of terephthaloyl chloride in 5000 parts by mass of n-butane as an organic phase solution; S4. Preparation of polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 400 parts by mass of aqueous solution, and then slowly drop 400 parts by mass of organic solution onto the surface of the aqueous solution to form an interface. After standing for reaction at room temperature for 10 minutes, open the valve at the bottom of the reactor and connect the vacuum pump, filter the thin film at the interface to the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 65°C for 7 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0029] Example 3: The following preparation scheme is used to obtain S1. Preparation of porous base membrane: Dissolve polyimide in N-methylpyrrolidone to prepare a casting solution with a mass fraction of 15%. Prepare a polymer porous membrane by non-solvent induced phase separation, and use it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2. Preparation of a covalent organic framework nanosheet dispersion by solvent thermal oxidation method: 3 parts by mass of 4,4'-diaminobiphenyl-3-sulfonic acid, 4.5 parts by mass of trialdehyde phloroglucinol and 0.3 parts by mass of diphenyl sulfone were dispersed in 3000 parts by mass of N,N-dimethylformamide, and heated at 120°C for 36 hours to obtain a covalent organic framework nanosheet dispersion; S3, preparing a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 8000 rpm for 15 minutes, take the supernatant and dialyze it with pure water at room temperature for 24 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, disperse 2.4 parts by mass of isophthaloyl chloride in 4000 parts by mass of cyclopentane as an organic phase solution; S4. Preparation of a polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 350 parts by mass of an aqueous solution, and then slowly drop 350 parts by mass of an organic solution onto the surface of the aqueous solution to form an interface. After standing for reaction at room temperature for 5 minutes, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface onto the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 70°C for 10 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0030] Example 4: The following preparation scheme is used to obtain S1. Preparation of porous base membrane: polytetrafluoroethylene is dissolved in dimethyl sulfoxide to prepare a casting solution with a mass fraction of 17%. A polymer porous membrane is prepared by non-solvent induced phase separation, and it is used as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2. Preparation of covalent organic framework nanosheet dispersion by solvent thermal oxidation method: 4 parts by mass of 4,4'-diaminobiphenyl-3-sulfonic acid, 6 parts by mass of 2,4,6-trialdehyde-1,3,5-triazine and 0.2 parts by mass of diethyl sulfone are dispersed in 4000 parts by mass of N,N-dimethylacetamide, and heated at 150° C. for 48 hours to obtain a covalent organic framework nanosheet dispersion; S3, preparing a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 9000 rpm for 10 minutes, take the supernatant and dialyze it with pure water at room temperature for 30 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, disperse 1.6 parts by mass of 3,3',5,5'-biphenyltetracarboxylic acid chloride in 3000 parts by mass of o-xylene as an organic phase solution; S4. Preparation of a polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 450 parts by mass of an aqueous solution, and then slowly drop 450 parts by mass of an organic solution onto the surface of the aqueous solution to form an interface. After standing at room temperature for 8 minutes, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface onto the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 75°C for 12 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0031] Example 5: The following preparation scheme is used to obtain S1. Preparation of porous base membrane: dissolve polyethersulfone in dimethyl sulfoxide to prepare a casting solution with a mass fraction of 20%. Prepare a polymer porous membrane by non-solvent induced phase separation, and use it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2. Preparation of a covalent organic framework nanosheet dispersion by a solvent thermal oxidation method: 5 parts by mass of 4,4'-diaminobiphenyl-3,3'-disulfonic acid, 7.5 parts by mass of 1,3,5-tris(4'-formaldehydephenyl)benzene and 0.1 parts by mass of dibutyl sulfone were dispersed in 5000 parts by mass of trichloroacetic acid, and heated at 150° C. for 36 hours to obtain a covalent organic framework nanosheet dispersion; S3, preparing a two-phase solution for interfacial polymerization: centrifuge the covalent organic framework nanosheet dispersion in S2 at a speed of 10000 rpm for 5 minutes, take the supernatant and dialyze it with pure water at room temperature for 36 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization. In addition, disperse 1.2 parts by mass of malonyl chloride in 2000 parts by mass of n-octanoic acid as an organic phase solution; S4. Preparation of a polyamide-type covalent organic framework membrane: soak the porous base membrane in S1 and fix it at the bottom of the reactor, pour in 500 parts by mass of an aqueous solution, and then slowly drop 500 parts by mass of an organic solution onto the surface of the aqueous solution to form an interface. After standing for reaction at room temperature for 3 minutes, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface onto the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 80°C for 15 minutes to obtain a polyamide-type covalent organic framework membrane for vanadium batteries.

[0032] Comparative Example 1: The amine monomer 2,5-diaminobenzenesulfonic acid containing a sulfonic acid group in Example 1 is replaced with an amine monomer p-phenylenediamine without a sulfonic acid group, and other preparation conditions remain unchanged.

[0033] Comparative Example 2: 400 parts by mass of the aqueous solution in step S3 of Example 2 were directly filtered onto the surface of a porous base membrane with a diameter of 4 cm to prepare a covalent organic framework membrane.

[0034] 1. Membrane pore size distribution test: The membrane in Example 1 was soaked in N,N-dimethylformamide to dissolve the lower porous base membrane, and the upper polyamide-type covalent organic framework thin layer was collected. After washing and drying with ethanol and pure water, the nitrogen adsorption-desorption isotherm of the polyamide-type covalent organic framework was tested using a specific surface area and porosity analyzer (Micrometrics ASAP 2460), and the pore size distribution was fitted using nonlocal density functional theory (NLDFT). The fitted average pore size results are shown in Table 1.

[0035] 2. Membrane proton conductivity test: The porous membranes prepared in Examples 1-5 and Comparative Examples 1-2 were tested for proton conductivity using an electrochemical workstation. The membrane was cut into a fixed size (1.2 cm × 1.2 cm), and after recording the thickness, it was placed in a fixture and pressed on both sides of the membrane with two silver sheets. Four electrodes were clamped on both ends of the exposed silver sheet, and the electrodes were connected to the electrochemical workstation. The voltage value was the open circuit voltage, and the frequency range was 100 kHz to 100 Hz. The proton conductivity σ can be calculated using the following formula: σ = L / (R × S) Wherein: R is the resistance of proton conduction; L is the distance between platinum wires; S is the product of the thickness and surface area of ​​the membrane. The test results are shown in Table 1.

[0036] 3. Characterization of membrane microstructure: The nanosheet dispersion in Example 1 and Example 2 was added dropwise to the surface of the anodized aluminum oxide (AAO) base membrane, and then dried for SEM characterization. The polyamide-like covalent organic framework membrane in Example 3 was subjected to surface and cross-sectional SEM characterization. Before characterization, the sample was subjected to gold spraying treatment to enhance conductivity for 40 seconds. The characterization results are shown in Figure 2. Figure 2-4 shown.

[0037] 4. Battery performance test: The membranes in Examples 1-5 and Comparative Examples 1-2 were assembled into battery stacks for testing, and the coulombic efficiency, voltage efficiency and energy efficiency were tested and recorded under the same operating conditions. The test results are shown in Table 1.

[0038] Table 1 Proton conductivity and battery performance test results

[0039] The preparation method and structure of the polyamide-type covalent organic framework diaphragm for vanadium batteries in Examples 1-5 are as follows Figure 1 The sulfur-oxygen double bonds of sulfoxides and sulfones added in the solvent thermal oxidation method can act as oxidants, destroying the carbon-nitrogen double bonds in the covalent organic framework structure of imines and reducing the interlayer forces, making them more inclined to form a thin sheet morphology ( Figure 2 and Figure 3 ). This shows that the solvent thermal oxidation method used in the present invention can achieve the transformation from monomer to covalent organic framework nanosheet in one step, improving the processability of the covalent organic framework. During the interfacial polymerization process, the exposed amino groups at the edge of the covalent organic framework nanosheet can react with the polyacyl chloride crosslinking agent to form a cross-linked network structure similar to polyamide, which has both the intrinsic pores of the covalent organic framework and the pores similar to polyamide. Figure 4 a in the figure is the surface of the covalent organic framework membrane in Example 3 of the present invention, Figure 4b is a cross-sectional scanning SEM image of the covalent organic framework diaphragm in Example 3 of the present invention. It can be seen that the surface of the polyamide-type covalent organic framework diaphragm presents a granular morphology without obvious defects. The cross-sectional SEM photo shows that the thickness of the polyamide covalent organic framework layer is about 90 microns. As shown in Table 1, in Comparative Example 1, the amine monomer containing sulfonic acid groups used in Example 1 is replaced with an amine monomer not containing sulfonic acid groups, and other conditions remain unchanged. The test results show that the voltage efficiency of the battery drops from 87.4% to 85.5%, which shows that the polyamide-type covalent organic framework diaphragm prepared by the present invention has a high porosity, and the pores are rich in sulfonic acid groups, which can improve the proton conductivity of the membrane, thereby improving the voltage efficiency of the vanadium battery. In addition, in Comparative Example 2, the aqueous phase solution (i.e., the covalent organic framework nanosheet aqueous solution) in Example 2 is directly filtered on the surface of the porous base membrane to prepare a membrane, which removes the cross-linking process of the interfacial polymerization of the nanosheets and the polyacyl chlorides, and only the intrinsic pores of the covalent organic framework exist. The test results show that the actual pore size of the separation layer in Comparative Example 2 is consistent with the theoretical pore size of the covalent organic framework itself, both of which are about 1.3 nm, while the actual pore size of the polyamide-type covalent organic framework layer in Example 2 is reduced to about 1.2 nm, thereby obtaining a higher coulombic efficiency. This shows that the polyamide-type covalent organic framework membrane prepared by the present invention has the intrinsic pores of the covalent organic framework and the polyamide pores, and the multi-level pore effect generated by the staggered arrangement reduces the effective pore size, thereby improving the ion selectivity of the membrane and the coulombic efficiency of the battery.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery, characterized in that: The steps include: S1, dissolving the polymer in solvent 1 to prepare a casting solution with a mass fraction of 10%-20%; using the casting solution to prepare a polymer porous membrane by non-solvent induced phase separation, and using it as a porous base membrane for preparing a polyamide-type covalent organic framework membrane; S2, dispersing 1-5 parts by weight of an amine monomer containing a sulfonic acid group, 1.5-7.5 parts by weight of an aldehyde monomer and 0.1-0.5 parts by weight of an oxidant in 1000-5000 parts by weight of solvent 2, and heating the mixture at 80-150° C. for 24-72 hours to obtain a covalent organic framework nanosheet dispersion; S3, centrifuging the covalent organic framework nanosheet dispersion in S2 at a speed of 6000-10000 rpm for 5-15 minutes, taking the supernatant and dialyzing it with pure water at room temperature for 12-36 hours to obtain a pure covalent organic framework nanosheet aqueous solution as an aqueous phase solution for interfacial polymerization; in addition, dispersing 0.8-3 parts by weight of a polyacyl chloride crosslinking agent in 1000-5000 parts by weight of solvent 3 as an organic phase solution; S4. Take the porous base membrane in S1 and immerse it at the bottom of the reactor, pour 300-500 parts by mass of aqueous solution, and then slowly drop 300-500 parts by mass of organic solution onto the surface of the aqueous solution to form an interface. After standing for 1-10 minutes at room temperature, open the valve at the bottom of the reactor and connect the vacuum pump to filter the thin film at the interface to the surface of the porous base membrane, and pour out the organic phase from the top. After taking out the membrane, wash it with ethanol and dry it at 60-80°C for 5-15 minutes to obtain a polyamide-type covalent organic framework diaphragm for vanadium batteries.

2. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S1, the polymer is selected from one of polyacrylonitrile, polyimide, polyvinylidene fluoride, polytetrafluoroethylene and polyether sulfone.

3. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S1, the solvent 1 is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

4. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S2, the amine monomer containing a sulfonic acid group is selected from one of 2,5-diaminobenzenesulfonic acid, 2,5-diamino-1,4-benzenedisulfonic acid, 4,4'-diaminobiphenyl-3-sulfonic acid and 4,4'-diaminobiphenyl-3,3'-disulfonic acid.

5. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S2, the aldehyde monomer is selected from one of trimesaldehyde, 2-hydroxy-1,3,5-benzenetricarbaldehyde, trialdehyde phloroglucinol, 2,4,6-trialdehyde-1,3,5-triazine and 1,3,5-tris(4'-formylphenyl)benzene.

6. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S2, the oxidant is selected from one of dimethyl sulfoxide, thionyl chloride, diphenyl sulfone, diethyl sulfone and dibutyl sulfone.

7. The method for preparing a polyamide-type covalent organic framework diaphragm for a vanadium battery according to claim 1, characterized in that: In step S2, the solvent 2 is selected from one of mesitylene, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide and trichloroacetic acid.

8. The method for preparing a polyamide-type covalent organic framework diaphragm for vanadium battery according to claim 1, characterized in that: In step S3, the polyacyl chloride cross-linking agent is selected from one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, 3,3',5,5'-biphenyltetracarboxylic acid chloride and malonyl chloride.

9. The method for preparing a polyamide-type covalent organic framework diaphragm for vanadium battery according to claim 1, characterized in that: In step S3, the solvent 3 is selected from one of n-hexane, n-butane, cyclopentane, o-xylene and n-octanoic acid.

10. A polyamide-type covalent organic framework diaphragm for vanadium battery, characterized in that: The covalent organic framework membrane is prepared by the method for preparing a polyamide-type covalent organic framework membrane for a vanadium battery as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyamide / COFs hybridized nanofiltration composite membrane and preparation method thereof

    CN105642133A

  • Preparation method of amide chain segment embedded covalent organic framework composite membrane and filter membrane thereof

    CN114146572A

  • Hollow fiber composite nanofiltration membrane based on COFs intermediate layer and preparation method of hollow fiber composite nanofiltration membrane

    CN115475538A

  • High-proton-conductivity porous diaphragm for vanadium battery and preparation method of high-proton-conductivity porous diaphragm

    CN117638128A

  • Preparation method and application of covalent organic framework nanofiltration membrane

    CN117717902A

Cited By

  • Covalent organic framework composite membrane as well as preparation method and application thereof

    CN120895674A